Cryogenic mechanical property and deformation behavior of a Ti-based metallic glass matrix composite by three point bending tests. (February 2018) - Wang, Y.S.; Gao, S.B.; Zhang, L.; Yuan, W.L.; Hao, G.J.; Lin, J.P.
Abstract: In this paper, cryogenic mechanical property and deformation behavior of a Ti-based metallic glass matrix composites (MGMCs) containing the in-situ β dendrite phase were investigated by three point bending tests from 298 K to 77 K. The result demonstrated that the flexural strength increased with the decreasing applied temperature, e.g. the flexural yielding strength increased by 32.6% from 1890 MPa at 298 K to 2506 MPa at 77 K, which has been fitted as an exponential function on the basis of the modified Zerilli and Armstrong (Z–A) model. It is found that the β dendrite phase lost its activity gradually and failed to promote shear-bands multiplication with decreasing testing temperature, leading to plasticity of the MGMC decreased. The deformation mechanism was discussed according to the fracture characteristics of the composite deformed at different cryogenic temperature. Highlights: Three point bending test was performed on a Ti-based MGM composite at cryogenic temperatures. The flexural strength of the alloy monotonously increased with the decreasing temperature. Dependence of yielding behavior governed by the dendrite on the applied temperature has been got. Plasticity of the composite decreased with reduction of applied temperature.